ANALISIS PERBEDAAN KINERJA KEUANGAN BANK SYARIAH MURNI DENGAN BANK SYARIAH CAMPURAN PADA TAHUN 2011 DENGAN MENGGUNAKAN METODE CAMEL : STUDI KASUS PADA BANK SYARIAH DISELURUH DUNIA - Nita Valliana Aprilini Achan; Anis Chariri (Diponegoro Journal of Accounting, 2014)
The development of Islamic banking is currently experiencing a rapid progress. Because Islamic banks are considered not susceptible to the mortgage crisis that hit financial markets around the world in 2008, there is a rapid development of Islamic banking. Consequently, many conventional banks are open or convert Islamic business. The rapid development of the bank is also marked by the performance and health of the bank.This research aims to determine the differences of financial performance between pure Islamic banking and a hybrid Islamic banking (Islamic branches of conventional bank) in 2011 around the world. Method of research from this thesis is using the method of hypothesis testing which conducted by non-parametric statistics testing, Two Independent Sample Test: Mann-Whitney U. The result showed that there is a significant difference regarding financial performance between pure Islamic banking and hybrid Islamic banking all around the world, especially from the ratio of KAP, BOPO and FDR. CAR, NPM and ROA ratio showed that there is no significant difference regarding financial performance of pure Islamic banking and hybrid Islamic banking.